Constraint of the results of modified Delphi study on enhancing the quality data input requirements of Life Cycle Cost (LCC) - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2013)
LCC process can be divided into three main categories, i.e. data inputs, conversion and outputs. However, critics have been made on the inadequacies of current methodology used in LCC practice, and the inaccuracies and poor quality of LCC outputs as very little emphasis has been given on the availability, accessibility, currency and reliability of data as inputs into the process of producing reliable LCC outputs. This paper reports part of a three-year programme of research to enhance quality of LCC outputs through the enhancement of quality data input requirements. The focus of quality data here is cost data inputs of building LCC. A modified Delphi approach was carried out to generate consensus of expert opinion regarding appropriate strategies to improve the availability, accessibility, currency and reliability of data as inputs for LCC by evaluating opinions and judgments from a group of experts that have experience, skills and knowledge in LCC. However, the results show there are relatively high numbers of strategies scored high levels of mean and low levels of standard deviation, which having the highest potential to be implemented, with the potential of a high achievement in improving the availability, accessibility, currency and reliability of data as inputs for LCC analysis. Because of the relatively high number of strategies which become constraint to the results of modified Delphi study, three procedures were implemented in the data analysis process to choose only top priority strategies that received the highest level of mean within that category of more than 3.75 for recommendation.